World Economic and Financial Surveys : Staff Studies, 1989. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1989)
This paper describes the functioning of labor markets and to eliminate other structural obstacles to noninflationary growth. The decline in the price level in the home country will involve a rise in the real money supply and, if output is sluggish, this will result in an excess supply of money. This, in turn, will lead to a drop in the domestic interest rate and, given foreign interest rates, to a temporary depreciation of the exchange rate. Structural measures could also affect investment and the current account by raising the rate of return on capital in the home country. If capital is internationally mobile, a higher rate of return on capital would result in a rise in investment and a temporary deterioration in the home country's current account, which will be financed by an inflow of foreign capital. The quantitative impact of financial market deregulation on the economy is rather uncertain.